Synthesis and Characterization of Some Bis Heterocyclic Compounds from (Dapson and 3-Amino Phenol) - Faez Abdul-Hussein Al-Rammahi (Journal of Global Pharma Technology, 2018)
This study involves synthesized of diheterocyclic compounds of the reaction of (4,4-diamino diphenylsulphon (DDS) and 3-Aminophenol with (benzoin, 2-Hydroxy-1,2-diphenylethanone); These compounds were characterized by melting point and FT-IR spectroscopy and the biologicl activity was evaluated against four kinds of bacteria two positive and two negative.Keywords: Heterocyclic compounds, Schiff base, Oxazepine, Imidazolidine, benzoin, Dapson.